2014
DOI: 10.1097/rhu.0000000000000148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Green Tea Extract on Serum Uric Acid and Urate Clearance in Healthy Individuals

Abstract: Objective: The objective of this study was to investigate the hypouricemic effects of green tea extract (GTE) in healthy individuals.Methods: This study comprised 1-week control, 2-week interventional, and 1-week follow-up periods. Participants were assigned randomly at the interventional period to consume GTE at 2 (GTE2), 4 (GTE4), or 6 (GTE6) g/d. Levels of serum uric acid (SUA), uric acid clearance, and serum antioxidant power (using trolox equivalent antioxidant capacity assay) were measured at both ends o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
(12 reference statements)
1
17
0
2
Order By: Relevance
“…Moreover, we found that pretreatment with EGCG significantly decreased the expression of Notch-1 and its downstream genes. When we were writing this paper, Jatuworapruk et al reported that EGCG could modestly lower serum uric acid (SUA) level and significantly elevated serum antioxidant capacity in healthy individuals [ 30 ]. These results, for the first time, provided a mechanistic link between the high levels of UA and the antioxidant and anti-inflammatory effects of EGCG.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that pretreatment with EGCG significantly decreased the expression of Notch-1 and its downstream genes. When we were writing this paper, Jatuworapruk et al reported that EGCG could modestly lower serum uric acid (SUA) level and significantly elevated serum antioxidant capacity in healthy individuals [ 30 ]. These results, for the first time, provided a mechanistic link between the high levels of UA and the antioxidant and anti-inflammatory effects of EGCG.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, green tea polyphenols were observed to reduce the expression of XO and renal urate transporters and to decrease serum UA concentrations in hyperuricemic mice [11]. In addition, green tea extract lowers serum UA concentrations in healthy individuals to some extent [12]. These studies together indicate a role for green tea catechins in UA metabolism.…”
Section: Introductionmentioning
confidence: 81%
“…Average changes in SUA were small < 0.2 mg/dl (< 5%) whereas the reduction in renal clearance were approximately 30%. [138].…”
Section: Evidence-basedmentioning
confidence: 99%